Albert the Great as a Scientist - Baňas, Ján (Organon F, 2006)
In the paper the author provides a brief sketch of Albert the Great as a scientist. By quoting passages from his works he shows that Albert the Great had a well-elaborated understanding of science. It is argued that in some aspects Albert was not too far from modern criteria that science and its methodology should meet. Accepting Aristotelian model of science, Albert stressed the need for experience and repeated observation in scientific research. While valuing authority, he examined carefully what it was stating and was not afraid to criticize even such an important authority as Aristotle, if his claims contradicted Albert’s observations. Although science was in close relation with theology, it wasn’t limited in its research and on the methodological level Albert was well aware of the need for their mutual independence. He was not afraid of providing science with freedom of inquiry, because he knew that in principle science and theology, if both sound, couldn’t contradict itself, because there is just one truth known from their different perspectives. The article also introduces Albert’s understading of and major contributions to mineralogy, astronomy, astrology, alchemy and other disciplines that were considered scientific in his time.